Analysis of Biochemical and Hematological Parameters During the First and Second Wave of SARS-CoV-2 Infection among North-East Indian Cancer Patients - Das, Sawmik; Sarma, Anupam; Das, Biki Chandra; Sarma, Dhruba Jyoti; Barman, Rashmisnata; Bhattacharyya, Mouchumee; Kataki, Amal Chandra; Rai, Avdhesh Kumar (Asian Pacific Journal of Cancer Care, 2022)
Introduction: SARS-CoV-2 (COVID-19) affects respiratory airways as well as the kidneys, hearts etc. This study aims to demonstrate the impact of COVID-19 infection on biochemical and hematological parameters in cancer patients of North-East India. Methods: The study includes biochemical parameters for 907 and hematological parameters for 1103 cancer patients who were tested for COVID-19 between 1st June 2020 and 1st June 2021. All the data were analyzed by the statistical software SPSS (ver20). Results: AST (p = 0.023), GGT (p = 0.026) and Urea (p = 0.004) significantly increased in COVID-19 positive cancer patients compared to negative cancer patients. Eosinophils (p=0.01), eosinophils absolute (p=0.01), monocyte (p=0.04) and MCHC (p=0.01) were significantly decreased in COVID-19 positive cancer patients compared to negative. Various biochemical and haematological parameters analysed in our study were found to be altered between the COVID-19 positive and negative group but their association was not found to be statistically significant. Conclusion: We conclude that in cancer patients of North-East India, significant alterations of biochemical and hematological parameters AST, GGT, Urea, Eosinophils, eosinophils absolute, monocyte and MCHC were found in COVID-19 positive cancer patients compared to negative cancer patients.